Analisis Rendahnya Motivasi Belajar Siswa terhadap Pembelajaran Bahasa Arab di Madrasah Aliyah Sidoarjo - Thoriq Imamul Musthofa; Muflihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low learning motivation in Arabic remains a major issue in many madrasahs, including Madrasah Aliyah Abil Hasan As-Syadzily Sidoarjo . Students exhibit low participation, weak self-confidence, and difficulty understanding materials. This study aims to analyze the causes of low motivation in learning Arabic and to formulate effective strategies for improving motivation among tenth-grade students. The research applied a qualitative descriptive approach, using open-ended questionnaires, semi-structured interviews, and classroom observations. Data were analyzed through Miles, Huberman, and Saldaña’s interactive model, consisting of data reduction, data display, and conclusion drawing.The findings indicate that low motivation is influenced by intrinsic factors, such as lack of interest, low self-confidence, and perceived language difficulty, as well as extrinsic factors, including monotonous teaching methods, limited learning media, and insufficient environmental support. These factors lead to decreased participation, academic performance, and increased language anxiety. Efforts to improve motivation can be achieved through communicative and contextual teaching methods, the use of digital media based on the ARCS model (Attention, Relevance, Confidence, Satisfaction), and strengthened social support from teachers and the madrasah environment. The study concludes that improving Arabic learning motivation requires a holistic approach integrating psychological, pedagogical, and social aspects to create meaningful and sustainable learning.